Forslag til endringer i reindriftsloven og konsekvenser for jordskifterettens oppgaver - Ravna, Øyvind (Fagbokforlaget, 2004)
In connection with the current process of change in the Reindeer Husbandry Act, The Reindeer Husbandry Legal Committe makes several proposals that bear on the formal competence of the Land Consolidation Court. According to the proposal, the Court will be allowed to examine rules related to defining reindeer husbandry districts, to prescribe rules related to the use of pastures, and formulate rules related to numbers of reindeers. The proposal gives the Land Consolidation Court a re-examination or appeal function of decisions made by an administrative body, modelled on section 33 in the last subsection of the Land Consolidation Act. The competence is manly limited to weighing the reasonableness of the rules or considering whether they conflict with rights acquired due to special legal considerations, most probably use since time immemorial, rights acquired by consuetude, or the like. The proposal outlines several challenges for the Land Consolidation Court: How to find the share ratio before re-examining prescribed rules, how to define rights acquired due to prescriptions or use since time immemorial, and how to elevate the factual competence among the Land consolidation judges.